2015
DOI: 10.1093/europace/euv313
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent alterations of Ca2+cycling in human cardiac hypertrophy and heart failure

Abstract: These data show that the SR Ca(2+) leak is lower in women than in men with comparable cardiac impairment. Since the SR Ca(2+) leak triggers delayed afterdepolarizations, our findings may explain why women are less prone to ventricular arrhythmias and confirm the rationale of therapeutic measures reducing the SR Ca(2+) leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
1
28
1
3
Order By: Relevance
“…Sarcoplasmic reticulum calcium leak is lower in ventricular myocytes isolated from women with heart failure than from men. 7 In association with this finding, a lower ratio of arrhythmic myocytes was observed in the female patients with heart failure. These sex differences may explain, in part, the lower incidence of spontaneous sustained ventricu- lar arrhythmias observed in women with heart failure in comparison with men.…”
Section: Sex Differences In Cardiac Electrophysiologymentioning
confidence: 62%
See 1 more Smart Citation
“…Sarcoplasmic reticulum calcium leak is lower in ventricular myocytes isolated from women with heart failure than from men. 7 In association with this finding, a lower ratio of arrhythmic myocytes was observed in the female patients with heart failure. These sex differences may explain, in part, the lower incidence of spontaneous sustained ventricu- lar arrhythmias observed in women with heart failure in comparison with men.…”
Section: Sex Differences In Cardiac Electrophysiologymentioning
confidence: 62%
“…Sex differences in ion channel expression/function, autonomic regulation, and intracellular calcium handling may also influence the substrate and triggers for ventricular arrhythmias. 1,7 Figure 6. Probability of VT/VF or death (A and C) and cumulative incidence of VT/VF (B and C) on the basis of sex and the etiology of heart disease.…”
Section: Arrhythmic Events In Icd Recipientsmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have suggested that high testosterone levels may have pro-arrhythmic effects through modulation of cardiac contraction and calcium homeostasis. [28][29][30][31] Other studies suggested that arrhythmias may occur due to higher adrenergic activity increasing apoptosis, which would worsen ARVC/D pathologies. 32,33 the arrhythmic potential in this specific disease constellation, since in our in vitro model, the healthy CMs did not show increased lipogenesis and apoptosis after 5F pathogenic induction.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work of our group demonstrated that the diastolic SR‐Ca 2+ leak is similar in human ischemic heart disease and dilated cardiomyopathy rendering significant effects of this difference on the outcomes of our study unlikely. The fact that the proportion of male patients is slightly lower in the HF‐Tx group compared with HF‐Im may even lead to an underestimation of this increase as male HF patients were shown to display a higher SR Ca 2+ leak compared with female patients (). Our paper additionally shows that the SR Ca 2+ leak can still be reduced by CaMKII inhibition at the stage of heart transplantation due to insufficient response to LVAD support.…”
Section: Discussionmentioning
confidence: 99%